The Influence of Subaltern Studies on Indian Historiography: a Study of Several Approaches - De Munck, Janina (Acta Orientalia Vilnensia, 2004)
The goal of this article is to evaluate the influence of Subaltern studies on contemporary Indian historiography. Subaltern studies, an offspring of the postmodern paradigm, offered a new program for studying Indian history, the main aim of which is to construct an authentic Indian history devoid of Eurocentric concepts. I analyse four texts (the authors of which do not belong to the Subaltern collective) that discuss postcolonial Indian historiography, in order to find out how well those authors are acquainted with Subaltern Studies and how the problems of history writing in India that they raise in their texts correlates with the problematics of Subaltern research. My analysis shows that the relation of native Indian historians with the Subaltern Studies is quite limited, because Subaltern scholars tend to rely on Western concepts to construct the authentic Indian history, an unfeasible project from the native Indian perspective.